Cost accounting : using a cost management approach - Rayburn, L.Gayle (Boston : McGraw-Hill / Irwin, 1996)
Business
2004-08-18
Keywords: Cost accounting; Managerial accounting; Cost behavior; Cost estimation; Budgeting; Cost management